Actualizing Ethnoscience in Physics Education: A New Pathway to Foster Academic Creativity through Local Traditions - Mayang Dela Kesumah; Ilham Falani; Haerul Pathoni; Muhammad Haris Effendi Hasibuan (Didaktika: Jurnal Kependidikan, 2025)
Strengthening academic creativity is an urgent need in 21st-century physics education, which is characterized by complex challenges and global changes. This study aims to actualize ethnoscience as a contextual approach that can enhance student creativity through the integration of local cultural values into physics learning. Using a combined framework of Systematic Literature Review (SLR) and field surveys, this study analyzed 10 relevant articles and collected quantitative data from 50 high school students. Descriptive and inferential analysis results show that positive perceptions of ethnoscience-based learning (r = 0.472) and appreciation of local culture (r = 0.352) are significantly related to high levels of student academic creativity. In addition, linear regression results reveal that these two variables together explain 31.3% of the variance in student creativity. These findings indicate that physics learning based on local wisdom is not only culturally relevant but also pedagogically effective in encouraging creative, reflective, and contextual thinking. Therefore, future educational strategies need to consider ethnoscience as a core approach in the design of culture-based curricula.